The Subversive Potential of Women's Relation to Work*. Issue 1 (2nd January 2017) - Galerand, Elsa; Kergoat, Danièle
ABSTRACT: This article makes the hypothesis that it is the relation to work, and not work itself, that holds subversive, or even liberating, potential for women. We begin by showing the theoretical convergence between this hypothesis and feminist epistemology. In order to test the hypothesis empirically, we then look at the paradoxical ways in which many women relate to paid work. In order to understand this paradox, we argue that it is necessary to go back to a feminist definition of work by calling into question the separation between professional and domestic work. Finally, we attempt to make suggestions to transform this subversive potential into collective emancipatory practices. We insist on the necessity for the feminist movement to put domestic work back at the center of its reflection on work and on the emancipation of women.